2019
DOI: 10.4049/immunohorizons.1800061
|View full text |Cite
|
Sign up to set email alerts
|

FliC’s Hypervariable D3 Domain Is Required for Robust Anti-Flagellin Primary Antibody Responses

Abstract: Bacterial flagellin is a well-known agonist of the innate immune system that induces proinflammatory responses through the TLR5 and Naip5/6 recognition pathways. Several clinical trials investigating flagellin fusion proteins have demonstrated promising results for inducing protective immunity toward influenza virus, which has been largely attributed to flagellin's ability to activate TLR5. Our laboratory previously demonstrated that the Salmonella enterica serovar Typhimurium flagellin protein, FliC, induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…To determine Ab production in mucosal secretions, two-weeks after the third vaccination, we collected BALF and determined FlaB-specific Ab responses by Western blot analysis. Since it has been reported that deletions of hypervariable region of Salmonella typhimurium FliC abrogates antibody-mediated neutralization [ 16 , 17 ], we employed FlaB ΔD2D3 as a control protein to investigate the role of 19 amino acids on the Ab production as well as Ag–Ab interaction profiles. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine Ab production in mucosal secretions, two-weeks after the third vaccination, we collected BALF and determined FlaB-specific Ab responses by Western blot analysis. Since it has been reported that deletions of hypervariable region of Salmonella typhimurium FliC abrogates antibody-mediated neutralization [ 16 , 17 ], we employed FlaB ΔD2D3 as a control protein to investigate the role of 19 amino acids on the Ab production as well as Ag–Ab interaction profiles. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To develop deimmunized FlaB, we targeted B-cell epitopes by using in silico prediction and structure modeling tools. It has been reported that deletions of hypervariable region of Salmonella typhimurium FliC abrogates antibody-mediated neutralization [ 16 ]. Our computational analyses also found that the most probable B-cell epitope would be located within hypervariable D2D3 regions (170–284 amino acid) of the FlaB molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flagella elicit the activation of host inflammatory responses via flagellin interaction with specific molecules through a variety of signaling pathways. Flagellins act as potent agonists of the innate immune system inducing proinflammatory responses, given their ability to stimulate the extracellular Toll-like receptor 5 (TLR5), the intracellular NOD-like receptor (NLR) family 4 (NLRC4)-NAIP 5/6 inflammasome, and an unknown additional third pathway recently proposed that is independent of TLR5, Casp1/11, and MyD88 ( Figure 7 ) [ 201 , 202 , 203 ].…”
Section: Filament–host Interactionmentioning
confidence: 99%
“…Mice immunized with FliC and different truncated versions made antibodies that showed reactivity to the D0/D1 and D2/D3 domains, indicating that both components of the molecule are antigenic. The D3 domain of FliC influences immunogenicity independently of the known innate recognition sites in the D0/D1 domains to augment antibody production, suggesting that full-length FliC and the preservation of all four domains would be critical for optimal immunogenicity and primary and secondary antibody responses in flagellin-based vaccines [ 203 ]. The nature of the third pathway is poorly understood and requires further investigation.…”
Section: Filament–host Interactionmentioning
confidence: 99%